2018
DOI: 10.1038/s41598-018-24409-9
|View full text |Cite
|
Sign up to set email alerts
|

Hippophae rhamnoides as novel phytogenic feed additive for broiler chickens at high altitude cold desert

Abstract: Extremes of climate and hypobaric hypoxia cause poor growth performance in broiler chickens at high altitude. The present study examined the potential of Hippophae rhamnoides extract as phytogenic feed additive for broilers reared at 3500 m above mean sea level (MSL). Higher content of phytomolecules were recorded during characterization of the extract. Immunomodulatory activity of extract was observed in chicken lymphocytes through in-vitro studies. Thereafter, for in vivo study, 105 day old Rhode Island Red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Since, camels graze on a hilly valley and plains which are flourishing with various herbal flora and especially seabuckthorne plant leaves. These plants are rich in many flavonoids and alkaloids phytomolecules having antioxidant properties [29]. Therefore, these phytomolecules may have beneficial effects on body metabolism and health of native livestock [29], including double humped camel through modulating body antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, camels graze on a hilly valley and plains which are flourishing with various herbal flora and especially seabuckthorne plant leaves. These plants are rich in many flavonoids and alkaloids phytomolecules having antioxidant properties [29]. Therefore, these phytomolecules may have beneficial effects on body metabolism and health of native livestock [29], including double humped camel through modulating body antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…These plants are rich in many flavonoids and alkaloids phytomolecules having antioxidant properties [29]. Therefore, these phytomolecules may have beneficial effects on body metabolism and health of native livestock [29], including double humped camel through modulating body antioxidant status. However, these factors need detailed investigation on how different phytomolecules affect the native camel's health and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Livability percentage was then calculated by using the formula ((total number of live birds after the experiment/Initial total number of birds) × 100). The economic efficiency of the dietary inclusion of alternative protein sources was calculated as the total costs needed to obtain one-kilogram BWG according to Kalia et al 12 . The European performance efficiency factor (EPEF) was calculated at the end of the experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…Papuc et al, (2009) reported in an in vitro study that sea buckthorn (H. rhamnoides) polyphenolic extract protected the refrigerated meat (beef and pork) against lipid peroxidation. Kalia et al, (2018) reported that H. rhamnoides extract is rich in flavonoids and its inclusion in the diet (200 mg/kg) improved the antioxidant defense level, increasing T-AOC and decreasing the MDA in the plasma of Rhode Island Red Cross-bred chicks reared at high altitude cold dessert. The same authors explained that those results could be attributed to the potentially synergistic effect of phenolic compounds and carotenoids contained.…”
Section: Liver Oxidative Stress Evaluationmentioning
confidence: 99%